Biorreator híbrido com membranas de ultrafiltração e osmose direta como alternativa para o tratamento e reúso do efluente de refinaria de petróleo - Priscila Barbosa Moser (2017)
The high water consumption and large production of effluents are characteristics of oil refineries. In the effluent are present aromatic hydrocarbons, nitrogenous compounds, sulfurous, phenolic, inorganic substances, heavy metals, cyanides, oil and greases. For water reuse purposes, tertiary treatment is needed, and thus new technologies have attracted interest from/in various sectors. Among them, the membrane separation processes (PSM), in particular, membrane bioreactors (MBR) stand out. Membrane fouling and the limitation in the removal of low molar mass compounds represent a challenge for such processes. Technologies such as forward osmosis (FO) and hybrid osmotic bioreactors (MBRO+UF) have received increasing attention from the academia and industry professionals as a means of overcoming these gaps, as well as increasing removal rates, with lower energy costs and high quality effluent. In this context, the present study aimed to evaluate the performance of FO and MBRO+UF for an oil refinery effluent treatment, evaluating the salinity effect on the biological system, membrane fouling, ultrafiltration flow rate (UF) and of FO, as well as the reverse osmosis (RO) use for permeate separation and the osmotic solution reconcentration. It was carried out on bench scale, characterization of several physicochemical parameters of the currents, as well as samples characterization of feed, permeate, biological sludge, supernatant and osmotic solution using Infrared Absorption spectroscopy and fluorescence Emission / Excitation matrix absorption spectroscopy. In addition, the sludge and membrane morphology were analyzed by microscopy techniques. The results indicate the importance of the UF use in order to alleviate the saline load in the biological system, being able to maintain the MBRO+UF efficiency, considering the effluent produced by the UF. By the hybrid system, removals were done above 99,9% of dissolved organic carbon (DOC), , showing the recalcitrant organic matter removal. This allows the effluent to be reused in cooling systems and boilers in oil refineries. It should be noted that, during the hybrid system monitoring, no fouling was observed on the FO membrane, which is why the membrane was not removed for cleaning. The FO flow ranged from 0.58 to 2.0 kg.h-1m2 and RO was efficient for the permeate separation, and for the osmotic solution reconcentration